Evaluation of nasal mucociliary clearance in rheumatoid arthritis: a comparative analysis using saccharin test - Deswal, Shelja; Yadav, Jyoti; Deswal, Mohit; Singh, Harpreet (International Journal of Research in Medical Sciences, 2017)
Background: Rheumatoid arthritis (RA) is a chronic multisystem disease of unknown etiology characterized by persistent inflammatory synovitis, usually involving peripheral joints in a symmetric distribution. RA is a systemic disease often associated with cutaneous and organ-specific extra-articular manifestations the mucociliary clearance system protects the lower respiratory system by trapping and removing inhaled pathogenic viruses and bacteria, in addition to nontoxic and toxic particulates (e.g., pollen, ash, mineral dust, mold spores, and organic particles), from the lungs. Effective clearance requires both ciliary activity and the appropriate balance of periciliary fluid and mucus. Methods: This was a case control study conducted in the Department of Physiology, Pt. B.D. Sharma PGIMS, Rohtak in 50 females of age group 30-50 years. Control group comprised of 25 healthy volunteer females while study group comprised of 25 rheumatoid arthritis female patients with disease duration of more than five years. Proven cases of RA (as per 1987 ACR criteria) were taken with disease duration of more than five years from Rheumatology clinic of Pt. B.D. Sharma PGIMS, Rohtak. Nasal mucociliary clearance time was evaluated by saccharin method. Results: The results of our study showed abnormal mucociliary clearance in rheumatoid arthritis patients. Conclusions: The study shows an abnormal mucociliary clearance in rheumatoid arthritis patients. Impairment of mucociliary clearance seems to be the result of qualitative and quantitative alterations in respiratory secretions.